The Operating Performance Tests of Power Unit A5 in TPP "Kolubara" in Load-Frequency Control - Pavlović, Jelena; Džepčeski, Dane; Stanojčić, Vladimir; Arnautović, Dušan; Bogdanović, Slobodan; Latinović, Aleksandar; Duboka, Dušan (Proceedings, Electrical engineering institute "Nikola Tesla", 2013)
As a result of significance of primary frequency control, as well as diversity of turbine-governing systems implementation, their possibilities, parameter settings, various operating conditions, operating modes and duration, there is a need for collection and systematization of data relevant to participation of each power unit in EPS in primary frequency control. In this purpose the turbine governor settings were experimentally determined. The subject of this paper are test results of participation quality of one thermal unit in primary frequency control, and also measurement results of turbine-governing system parameters, on which parameters of mathematical model of turbine governor and thermal power unit as an element of the power system are calculated.